Cycle of Potential Fishing Area of WPP-NRI 711 Year 2011-2020 - Pratama, Septian Surya; Kushadiwijayanto, Arie Antasari; Risko, Risko (Jurnal Laut Khatulistiwa, 2023)
This study discussed the cycle of potential fishing areas in WPP-NRI 711 based on the distribution of Sea Surface Temperature (SST) and distribution of chlorophyll-a concentration using MODIS Aqua satellite imagery. The distribution of Potential Fishing Areas (PFA) was determined based on the distribution of the thermal front which was processed using MGET (Marine Geospatial Ecology Tools) and chlorophyll-a. Determination of fluctuations and the emergence period of PFA for 10 years (2011-2020) is carried out using wavelets. The results showed that the average SST in WPP-NRI 711 was 29 °C. The highest average SST is 31 °C in May of the Transitional I Season, and the lowest average temperature is 27.9 °C in February of the West Monsoon Season. The average chlorophyll-a concentration was 0.6 mg/m3, the highest average chlorophyll-a concentration was 0.76 mg/m3 in December West Monsoon Season, and the lowest average was 0.53 mg/m3 in October Transitional II Season. The average PFA distribution area is 1.111 km2, the highest average area is 1.324 km2 in the West Monsoon Season, then the lowest area is 924 km2 in the Transitional II Season. Based on global spectrum and wavelet analysis, it is known that the period of the appearance of PFA is 3-6 months or Seasonal. then in the Northern Region segment of WPP-NRI 711, covering the Natuna Sea, the appearance of PFA is strongly influenced by Seasonal current movements. Meanwhile in the southern part, including the Karimata Strait, the emergence of PFA is strongly influenced by river runoff and changing Seasons.